2020
DOI: 10.3390/ijms21144846
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Chlorophyll Fluorescence of Photosystem II Performance during Drought and Heat Stress is Associated with the Antioxidant Capacities of C3 Sunflower and C4 Maize Varieties

Abstract: Agricultural production is predicted to be adversely affected by an increase in drought and heatwaves. Drought and heat damage cellular membranes, such as the thylakoid membranes where photosystem II occurs (PSII). We investigated the chlorophyll fluorescence (ChlF) of PSII, photosynthetic pigments, membrane damage, and the activity of protective antioxidants in drought-tolerant and -sensitive varieties of C3 sunflower and C4 maize grown at 20/25 and 30/35 °C. Drought-tolerant varieties retained PSII e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 82 publications
(147 reference statements)
4
34
0
1
Order By: Relevance
“…Therefore, malondialdehyde (MDA) a product of polyunsaturated lipids degradation, is a widely used marker of oxidative lipid injury caused by environmental stress. Several studies confirmed the increase of MDA content in plant leaves under different stress conditions (Jbir‐Koubaa et al, 2015; Jin et al, 2010; Killi et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, malondialdehyde (MDA) a product of polyunsaturated lipids degradation, is a widely used marker of oxidative lipid injury caused by environmental stress. Several studies confirmed the increase of MDA content in plant leaves under different stress conditions (Jbir‐Koubaa et al, 2015; Jin et al, 2010; Killi et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…suppressing photorespiration (Killi et al, 2017(Killi et al, , 2020. Water scarcity is known to affect the electron transport chain through inhibition of D1 synthesis and damages to the oxygen-evolving complex in the PSII and in the reaction centers of both PSII and PSI (Dalal and Tripathy, 2018;Wang et al, 2018).…”
Section: Hussain Et Al 2019mentioning
confidence: 99%
“…Under thermal stress, photosynthesis in C4 plants shows a greater tolerance than in plants with C3 metabolism, associated with the accumulation of oxaloacetic acid within the bundle sheath cells. This process effectively concentrates CO 2 at the carboxylation site of Rubisco, suppressing photorespiration ( Killi et al, 2017 , 2020 ). Water scarcity is known to affect the electron transport chain through inhibition of D1 synthesis and damages to the oxygen-evolving complex in the PSII and in the reaction centers of both PSII and PSI ( Dalal and Tripathy, 2018 ; Wang et al, 2018 ).…”
Section: Physiological Responses To the Combination Of Heat And Drought Stress In Maizementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Usman et al (2018) reported the role of HSP70 in membrane stability in chili pepper. Also, the accumulation of ROS upon heat stress leads to the accumulation of thiobarbituric acid derivatives leading to membrane lipid damages, and subsequently the electrolyte leakage (Killi et al, 2020). The extent of differences observed in HSP70 expression, membrane stability, and lipid peroxidation can be used to improve the thermotolerance capacity of the genotypes.…”
Section: Response Of Pearl Millet Genotypes To Heat Stressmentioning
confidence: 99%